2009
DOI: 10.1002/bip.21179
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the human cannabinoid receptor one carboxyl‐terminus identifies two amphipathic helices

Abstract: Recent research has implicated the C-terminus of G-protein coupled receptors in key events such as receptor activation and subsequent intracellular sorting, yet obtaining structural information of the entire C-tail has proven a formidable task. Here, a peptide corresponding to the full-length C-tail of the human CB1 receptor (residues 400–472) was expressed in E.coli and purified in a soluble form. Circular dichroism (CD) spectroscopy revealed that the peptide adopts an α-helical conformation in negatively cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(85 citation statements)
references
References 53 publications
12
71
2
Order By: Relevance
“…In running Modeler on the C terminus, only the unstructured regions were explored; Ala-440 -Met-461 were modeled as an ␣-helix that would be parallel to a lipid bilayer (i.e. the same plane as Helix 8); this is consistent with NMR results that suggest the existence of "Helix 9" in the C terminus (31).…”
Section: Docking Of Phr015 In the Presence Of Cp55940-supporting
confidence: 54%
“…In running Modeler on the C terminus, only the unstructured regions were explored; Ala-440 -Met-461 were modeled as an ␣-helix that would be parallel to a lipid bilayer (i.e. the same plane as Helix 8); this is consistent with NMR results that suggest the existence of "Helix 9" in the C terminus (31).…”
Section: Docking Of Phr015 In the Presence Of Cp55940-supporting
confidence: 54%
“…Our molecular dynamics simulations (27) and SDSL/EPR results (3) further demonstrate that TMH7's intramembrane conformation and relative orientation with respect to H8 are dynamically modulated by its membrane environment. A final characteristic of hCB1(TMH7/H8) germaine to the present work, as first defined by us (4,27) and substantiated by others (30), is the amphipathicity of H8: the relative disposition therein of a hydrophilic cationic cluster contralateral to a hydrophobic "face" of nonpolar residues is likely important for optimal H8 orientation/interaction with both the plasma membrane and the G-protein subunits to which hCB1 couples for information transmission and intracellular signal propagation.…”
Section: Precedent For the Current Work: Key Structural Features Of Hmentioning
confidence: 81%
“…The relatively limited homology between rhodopsin and hCB1-particularly with respect to their C-terminal domain-precludes direct extrapolation of the rhodopsin structure to hCB1 (25,26). Our and others' investigations on hCB1 higherorder structure indicate that H8 acquires a helical conformation in membrane-mimetic environments with a juxtamembrane orientation parallel to the membrane surface and perpendicular to the TMH7 intramembrane bundle (4,(27)(28)(29)(30). Multiple electrostatic amino-acid interactions underpin TMH7/H8 conformation (4), and interactions between these two hCB1 α-helical segments have been implicated in ligandinduced hCB1 conformational transitioning (3).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…C-terminal truncation experiments from the Mackie laboratory (Jin et al, 1999) have shown that CB 1 (with truncation at C417) signals normally in the presence of agonists. With the exception of helix 8, the C terminus is largely unstructured, though recent work on an isolated C-terminal peptide suggests the existence of an additional C-terminal helix, helix 9 (Ahn et al, 2009b). However, recent results from the Mackie laboratory (Straiker et al, 2012) reinforce that the functional significance of the C terminus pertains to desensitization and receptor internalizationnot necessarily to receptor signaling by heterotrimeric G proteins.…”
Section: Molecular Modelingmentioning
confidence: 99%